Review of the application of Cu-containing SSZ-13 in NH3-SCR-DeNOx and NH3-SCO - Jabłońska, Magdalena (RSC advances, 2022)
The reduction of NOx emissions has become one of the most important subjects in environmental protection. Cu-containing SSZ-13 is currently the state-of-the-art catalyst for the selective catalytic reduction of NOx with ammonia (NH3-SCR-DeNOx). Although the current-generation catalysts reveal enhanced activity and remarkable hydrothermal stability, still open challenges appear. Thus, this review focuses on the progress of Cu-containing SSZ-13 regarding preparation methods, hydrothermal resistance and poisoning as well as reaction mechanisms in NH3-SCR-DeNOx. Remarkably, the paper reviews also the progress of Cu-containing SSZ-13 in the selective ammonia oxidation into nitrogen and water vapor (NH3-SCO). The dynamics in the NH3-SCR-DeNOx and NH3-SCO fields make this review timely.